Modelling and performance evaluation of an HV impulse test arrangement with HVDC bias - Shifidi, S. K. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.